Research on lubrication properties of selected raw plant and animal materials - Gardyński, Leszek; Kałdonek, Jolanta (Transport, 2020)
The article presents the results of research on lubrication properties of rapeseed oil, methyl esters of rapeseed oil, as well as esters with goose fat. Rapeseed oil has a better lubrication properties in relation to methyl esters of rapeseed oil. Addition of goose fat to esters negatively affected their lubrication properties. The presented results confirm a relationship between the degree of unsaturated and lubricated properties. Among the tested compounds with oxygen groups (COOH, COOCH3, C = O), the oleic acid (with a COOH group) characterised the best lubricity. The fat goose, which contains the least amount of unsaturated fatty acid esters, proved to be ineffective addition lubricity between the factor lubricants analysis.